Evaluating the effect of birth weight on brain volumes and depression: An observational and genetic study using UK Biobank cohort. Issue 1 (2020) - Ye, Jing; Wu, Cuiyan; Chu, Xiaomeng; Wen, Yan; Li, Ping; Cheng, Bolun; Cheng, Shiqiang; Liu, Li; Zhang, Lu; Ma, Mei; Qi, Xin; Liang, Chujun; et al.
Abstract: Background: Birth weight influences not only brain development, but also mental health outcomes, including depression, but the underlying mechanism is unclear. Methods: The phenotypic data of 12, 872–91, 009 participants (59.18–63.38% women) from UK Biobank were included to test the associations between the birth weight, depression, and brain volumes through the linear and logistic regression models. As birth weight is highly heritable, the polygenic risk scores (PRSs) of birth weight were calculated from the UK Biobank cohort (154, 539 participants, 56.90% women) to estimate the effect of birth weight-related genetic variation on the development of depression and brain volumes. Finally, the mediation analyses of step approach and mediation analysis were used to estimate the role of brain volumes in the association between birth weight and depression. All analyses were conducted sex stratified to assess sex-specific role in the associations. Result: We observed associations between birth weight and depression (odds ratio [OR] = 0.968, 95% confidence interval [CI] = 0.957–0.979, p = 2.29 × 10 −6 ). Positive associations were observed between birth weight and brain volumes, such as gray matter ( B = 0.131, p = 3.51 × 10 −74 ) and white matter ( B = 0.129, p = 1.67 × 10 −74 ). Depression was also associated with brain volume, such as left thalamus (OR = 0.891, 95% CI = 0.850–0.933, p = 4.46 × 10 −5 ) and right thalamus (OR = 0.884, 95% CI = 0.841–0.928, p = 2.67 × 10 −5 ). Additionally, significant mediation effects of brain volume were found for the associations between birth weight and depression through steps approach and mediation analysis, such as gray matter ( B = –0.220, p = 0.020) and right thalamus ( B = –0.207, p = 0.014). Conclusions: Our results showed the associations among birth weight, depression, and brain volumes, and the mediation effect of brain volumes also provide evidence for the sex-specific of associations.